Physicochemical properties of chitosan–magnetite nanocomposites obtained with different pH - Chapa, Christian (2021)
The physicochemical properties of the nanoparticle surface determine the performance of nanocomposites in biomedical applications such as their biodistribution and pharmacokinetics. The physicochemical properties of chitosan, such as apparent charge density and solubility, are pH dependent. Similarly, Fe3O4 nanoparticles are susceptible to variations in their physicochemical properties due to changes in pH. In this work, we evaluated the physicochemical properties of chitosan–magnetite nanocomposites that were suspended at pH 7.0, 9.0, and 11.0 to determinate the effect on particle size, zeta potential, and mass percentage of the polymeric coating, in addition to the crystalline phase and magnetic properties of magnetite phase. X-ray diffraction results exposed that the present phase was magnetite with no other phases present and that the crystallite size was between 10.8 and 14.1 nm. Fourier transform infrared verified the chitosan functional groups in treated samples while the percentage of mass determined by TGA found to be nearly 9%. Scanning electron microscopy micrographs corroborated the spherical shape of the bare and chitosan-coated nanoparticles. Dynamic light scattering results showed that chitosan coating modifies the zeta potential, going from a potential of −11.8 mV for bare particles to −3.0 mV (pH 11). Besides, vibrating sample magnetometer measurements showed that coercivity remained very low, which is desirable in biomedical applications.